The Correlation between Clean and Healthy Living Behavior and Diarrhea Incidence in Children Under Five Years Old: A Literature Review Study - Dwiana Mei Desti Setyarini; Nur Hidaayah (Universitas Nahdlatul Ulama Surabaya, 2022)
Diarrhea is a disease often accompanied by mortality and morbidity. Its incidence increased 1% per year from 300 thousand household samples. Lack of Clean and Healthy Living Behavior (in Indonesia, namely of a program is Perilaku Hidup Bersih Sehat or PHBS) can affect the incidence of diarrhea. This paper analyzes the correlation between PHBS and diarrhea incidence in children under five years old. The four PHBS indicators are exclusive breastfeeding, healthy latrines, clean water, and handwashing with soap (HWS). This research was a literature review study. We used a database of google scholar and the garuda portal. In addition, journal screening included three stages. The first stage was the selection of free access journals. Then, the second stage was the selection of titles and abstracts according to the keywords (PHBS, Diarrhea, and Children under five years old) and publication year. The third stage was selecting the background, method, results, and discussion. Eleven papers explained the correlation between the PHBS and diarrhea incidence in children under five. There were five articles revealing the association between the incidence of diarrhea and four PBHS indicators. In addition, PHBS indicators most associated with diarrhea sequentially were handwashing with soap (11 publications), exclusive breastfeeding (10 journals), healthy latrines (8 papers), and clean water (6 documents). In conclusion, exclusive breastfeeding, clean water, healthy latrines, and handwashing with soap correlate to diarrhea incidence in children under five years old. Health workers should provide health education regarding PHBS.